Revitalizing Tradition Toward Islamic Modernity in Ṭāhā ʿAbd al-Raḥmān’s Though - Ikrom Mausuli (An-Nur International Journal of Islamic Thought, 2024)
The discussion of turāth and modernity is a never-ending topic in contemporary Islamic thought. In contrast to secular scholars like Abed al-Jābirī and Ḥasan Ḥanafī, who used materialist and phenomenological methods in reading turāth, Ṭāhā ʿAbd al-Raḥmān employs a logic and linguistic method with ethical and spiritual approaches. Through this process, he seeks to formulate Islamic modernity instead of following Western modernity, which he critiques intensively in the works of Islamic thinkers such as al-Jābirī. This article traces Ṭāhā's way of creating Islamic modernity through turāth as a milestone, providing an analysis and critique of Ṭāhā's thought on turāth and contributing to the realization of the idea of Islamic modernity.